PENGELOLAAN PEMBELAJARAN KITAB KUNING TINGKAT WUSTHO DI PONDOK PESANTREN SALAFIYAH IQRO - Khaalishah, Nor; Sapuadi, Sapuadi; Riyadi, Slamet (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The learning of classical Islamic texts (kitab kuning) serves as the core of salafiyah pesantren education, functioning to develop students’ linguistic competence, religious understanding, and character formation. This study aims to describe the management of kitab kuning learning at the Wustho level in Pondok Pesantren Salafiyah Iqro Palangka Raya, which represents an important transitional stage between basic learning and more advanced textual comprehension. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings indicate that learning management is carried out through internal deliberation and benchmarking activities, involving the selection of materials, scheduling, and mapping students’ abilities. The learning process is conducted systematically every day using traditional pesantren methods applied consistently. Evaluation is conducted through semester examinations and report cards, which function as feedback for improving subsequent learning. These findings highlight that the learning management at the Wustho level has been implemented systematically, although further strengthening is needed in planning and pedagogical innovation to make it more adaptive to students’ needs and the development of contemporary Islamic education.